Synthesis and mechanical and thermal properties of (Cr, Mn)2AlC solid solutions. (3rd April 2017) - Li, Haolin; Li, Shibo; Mao, Huan; Zhou, Yang
ABSTRACT: (Cr, Mn)2 AlC solid solutions have attracted much attention due to their magnetic property which will be enhanced with increasing Mn solubility. So far, only 3 at.-% Mn solubility in (Cr, Mn)2 AlC bulk materials has been reported. This work reports on the synthesis of (Cr, Mn)2 AlC solid solutions via a new reaction route with AlCr2, C and Mn as starting materials. The Mn solubility increases with increasing the starting Mn content. The maximum solubility of Mn in (Cr, Mn)2 AlC was 8.3 at.-%, corresponding to a resultant solid solution (Cr0.83 Mn0.17 )2 AlC. However, increasing the Mn content in the starting mixture caused the formation of impurities in the sintered samples. A dense (Cr0.95 Mn0.05 )2 AlC ceramic has been achieved by hot-pressing the mixture of AlCr2 /C/0.1Mn. The mechanical properties and thermal expansion coefficient of (Cr0.95 Mn0.05 )2 AlC were measured.